Is a new EU wine policy coming? The unexpected role of regulatory measures - Eugenio Pomarici; Roberta Sardone (Wine Economics and Policy, 2022)
On January 1, 2023, a "reformed" Common Agricultural Policy (CAP) will come into force, which is innovative by nature in structural terms, and focused on environmental and social sustainability issues, aimed at a comprehensive digitization-based modernization of the agri-food sector. The new CAP keeps the current structure based on expenditure and regulatory measures, but includes a new planning tool, the national CAP Strategic Plan, a new CAP management model, and the new delivery model (NDM). Concerning EU wine policy, the new regulations foresee a number of specific amendments to existing rules, including changes that will apply to financial support for the wine sector with a reduced budget and to the regulatory measures. Among the latter, the most globally impacting are labelling rules, which require more information to consumers and allow the use of an e-label, the use of hybrid grape varieties for the production of appellation wines, and the inclusion among CAP regulated products of partially or totally de-alcoholised wines.
Keywords: 330; common agricultural policy; de-alcoholised wine; hybrid grape varieties; labelling